Prevalence of fatigue and depression in ALS patients and change over time. Issue 10 (17th September 2009) - McElhiney, M C; Rabkin, J G; Gordon, P H; Goetz, R; Mitsumoto, H
Abstract : Background: Amyotrophic lateral sclerosis (ALS) patients report both fatigue and depression. It is not clear how frequently each occurs, to what extent they occur together, how each relates to ALS disease status, or their stability over time. Objective: To assess frequency and persistence of fatigue and depression, and relationship to ALS disease status, for patients attending an ALS interdisciplinary centre for routine 3-month visits. Method: Measures included the Fatigue Severity Scale, Patient Health Questionnaire-9. ALS Functional Rating Scale—Revised and forced vital capacity, rate of disease progression, and bulbar/nonbulbar disease onset. Results: 223 patients completed the ratings once; of these, 113 completed them twice, and 65 on three visits. At baseline, 44% (99/223) had clinically significant fatigue, including 34 patients who also had a depressive disorder; 7% (16/223) had major or minor depression only, and 48% (108/223) had neither condition. Fatigue was associated with greater ALS severity, but depression was not. Among the 113 patients seen 3 months later, 75% (33/44) who were fatigued at Time 1 remained fatigued, while 48% (10/21) remained depressed. New-onset fatigue was reported by 22% (25/113), and new-onset depression by 6% (7/113). For the 65 patients seen a third time, rates remained nearly the same. Conclusion: Fatigue was more prevalent and persistent than depression, although 15% (34/223) of patients had both conditions. Fatigue but not depression was associated with ALS severity. The two conditions appear to be independent, although sometimes co-occurring, and both warrant consideration in evaluating patient functioning and treatment.